2018
DOI: 10.1186/s12979-018-0116-9
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies against 1940s era a/H1N1 influenza strains a/Weiss/43 and a/FM/1/47 and heterotypic responses after seasonal vaccination of an elderly Spanish population

Abstract: Background and methods: Elderly people have experienced several influenza natural infections and seasonal vaccinations during their lives. The aim of this work was to evaluate in an elderly Spanish population the presence of antibodies (Abs) against some 1940s era A/H1N1 influenza viruses and some new influenza viruses. We also evaluated the homologous and heterotypic responses after seasonal influenza vaccination. We collected pre-and post-vaccination serum samples from 174 elderly people (≥65 years) who were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
0
3
0
2
Order By: Relevance
“…Upon exposure to new drifted or shifted strains, the immune system recognizes the conserved epitopes and back-boosts memory cells from the first infections, generating antibodies that recognize common epitopes rather than create de novo protective responses from naïve B cell populations [28]. In our study, in both of the elderly cohorts the youngest person would have been born before 1953, so they would have been first imprinted with the classical A(H1N1) strains that circulated in the first half of the 20th century, which, as some studies have shown, share at least a 70% genetic and antigenic similarity with the A(H1N1)pdm09 subtype [7,29,30]. However, this phenomenon has not been observed in the group vaccinated with the AIV, which presents a comparable although significantly higher median age than the NAIV group (81 years versus 75 years); so, as far as we are concerned, we ignored any singularity that stimulates the occurrence of this phenomenon.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Upon exposure to new drifted or shifted strains, the immune system recognizes the conserved epitopes and back-boosts memory cells from the first infections, generating antibodies that recognize common epitopes rather than create de novo protective responses from naïve B cell populations [28]. In our study, in both of the elderly cohorts the youngest person would have been born before 1953, so they would have been first imprinted with the classical A(H1N1) strains that circulated in the first half of the 20th century, which, as some studies have shown, share at least a 70% genetic and antigenic similarity with the A(H1N1)pdm09 subtype [7,29,30]. However, this phenomenon has not been observed in the group vaccinated with the AIV, which presents a comparable although significantly higher median age than the NAIV group (81 years versus 75 years); so, as far as we are concerned, we ignored any singularity that stimulates the occurrence of this phenomenon.…”
Section: Discussionmentioning
confidence: 68%
“…At the present time, there are different influenza vaccines being used across the world, which differ in the way of manufacturing (eggs or cell culture), the number of influenza viruses included (trivalent and quadrivalent) and also based on their capacity to enhance the immune response on the population vaccinated (adjuvanted and non-adjuvanted), among others. Adjuvanted influenza vaccines (AIV) are designed to enhance immune responses, and usually they are employed in certain risk groups that need higher protection, like the elderly [6,7]. The adjuvants contained in this kind of vaccine increase the immune response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Los métodos empleados para su medida y los correlatos de seroprotección frente a la HA que deben utilizarse para evaluar la eficacia de las vacunas antigripales son objeto de debate actual. En el NIC de Valladolid se ha demostrado en trabajos recientes que las vacunas estacionales antigripales son capaces de producir respuestas humorales heterotípicas frente a virus no contenidos en su composición (100,141,142).…”
Section: Discusión Discusiónunclassified
“…Las reacciones heterotípicas entre diferentes cepas de virus de la gripe, o incluso entre diferentes subtipos es frecuente. Existen trabajos que demuestran la existencia de respuestas cruzadas entre cepas diferentes de un mismo subtipo, tanto en la HA (47,100,105,141,142) como en la NA (155). La variabilidad de la HA es un logaritmo superior en magnitud a la de la NA (11), por lo que sería esperable, y parece confirmarse en este trabajo, que las respuestas heterotípicas de Acs frente a la NA pueden ser incluso más frecuentes.…”
Section: Estudio De Acs Anti-na Previos a La Vacunaciónunclassified